(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Systemic acquired resistance (SAR) or generated systemic resistance is researched via local plant–microbe interactions (ISR). Pathogens on leaves induce SAR, whereas plant-helping microbes on roots create ISR. SAR includes salicylic acid (SA), but other signals enhance the immune system. SAR and maybe ISR-related signalling networks govern the immune system via these signals. N-hydroxy-pipecolic acid (pipecolic acid) drives non-SA SAR. When plants are stimulated by SAR, they release volatile organic chemicals that other plants use as defensive signals to control the spread of defences between plants. SAR and ISR affect how phytohormones work together to make plants more resistant to pathogens and change the way their microbiomes are made up. Plant defence, interactions between plants and microorganisms, and interactions between plants may change. So, interactions between organisms can be used together to protect plants in a very effective way.